Theory of Mind as a Mediator of Reading Comprehension Differences between Chinese School-Age Children with Autism and Typically Developing Peers. (3rd July 2020) - Tong, Shelley Xiuli; Wong, Ruby Wing Yan; Kwan, Joyce Lok Yin; Arciuli, Joanne
ABSTRACT: This study examined the relation between Theory of Mind (ToM) and reading comprehension in 42 7- to 9-year-old Hong Kong Chinese children with autism and 55 typically developing peers (TD) who were comparable in age, nonverbal intelligence, and working memory. Relative to their TD peers, children with autism exhibited difficulties with reading comprehension and advanced ToM tasks, but not word reading and basic ToM tasks. After controlling for nonverbal intelligence, working memory, word reading, and vocabulary knowledge, ToM partially mediated the relation between group status (autistic or not) and reading comprehension. This mediation was significant for non-literal comprehension skills (i.e., those involving inference, evaluation, and mentalization) but not for literal comprehension skills (i.e., those involving simple recall and recognition of textually explicit information). These findings indicate that ToM partially explains the differences in non-literal reading comprehension between children with autism and their TD peers.